Perbandingan Tingkat Fertilitas Sapi Simmental dan Limousin di Peternakan Rakyat - Rizal Jayadi (Journal of Animal Husbandry, 2025)
This study compares the fertility performance of Simmental and Limousin cattle raised under smallholder farming systems. The objective was to evaluate reproductive parameters such as conception rate, service per conception, calving interval, and estrus return. A total of 120 cows were observed over a 12‑month period using field survey and reproductive record analysis. Results showed that Simmental cows exhibited higher conception rates and shorter calving intervals compared to Limousin cows, indicating better adaptability to smallholder management environments. The findings highlight the importance of breed selection for improving reproductive efficiency in rural cattle production systems.